Timeline Storyteller: The Design & Deployment of an Interactive Authoring Tool for Expressive Timeline Narratives - Brehmer, Matthew; Lee, Bongshin; Henry Riche, Nathalie; Tittsworth, David; Lytvynets, Kate; Edge, Darren; White, Chris (Computation+Journalism Symposium, 2019)
Timeline Storyteller (timelinestoryteller.com) is an open-sourced interactive application for authoring expressive visualization-based narratives about event sequences. Its design reflects a recently proposed timeline design space, which itself is grounded in an extensive survey. In this paper, we highlight its capabilities and reflect upon its usage and adoption.